2014
DOI: 10.11646/zootaxa.3847.3.2
|View full text |Cite
|
Sign up to set email alerts
|

An annotated checklist of Lithobiomorpha of China

Abstract: The lithobiomorph centipede fauna of China is listed here based on literature data. A total of 68 species in 15 genera/subgenera in 2 families, Henicopidae and Lithobiidae, has been recorded from China. Three genera and forty-four species are known only from China, including the monotypic genera Pterygotergum and Hedinobius. The original descriptions of 16 nominal species were based on specimens of single sex only and 13 nominal species of Lithobius have never been allocated to a subgenus. Lithobius (Lithobius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…This paper is based on the material collected by A.A. DISTRIBUTION. This species is known from Kirgizia (Issyk-Kul Region), Russia (Republic of Buryatia), North China and northern, western (including Govi-Altai and BayanÖlgii Aimags) and central parts Mongolia (Loksa, 1965(Loksa, , 1978Zalesskaja, 1978;Ma et al, 2014;Poloczek et al, 2016). Here L. giganteus is firstly recorded from Khovd Aimag.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…This paper is based on the material collected by A.A. DISTRIBUTION. This species is known from Kirgizia (Issyk-Kul Region), Russia (Republic of Buryatia), North China and northern, western (including Govi-Altai and BayanÖlgii Aimags) and central parts Mongolia (Loksa, 1965(Loksa, , 1978Zalesskaja, 1978;Ma et al, 2014;Poloczek et al, 2016). Here L. giganteus is firstly recorded from Khovd Aimag.…”
mentioning
confidence: 94%
“…Приведены данные о распространении и биотопическом распределении слабо изученного Schizotergitius altajicus Loksa, 1978. The centipede fauna of the Mongolian part of Altai and adjacent territories is insufficiently studied. Six species are known from Xinjiang (China) (Ma et al, 2014) and 15 species from Altai Republic in Russia (Zalesskaja, 1978;Nefediev et al, 2016Nefediev et al, , 2017a. Ten species of centipedes are known from the best studied northern part of Mongolia (Poloczek et al, 2016), while only six species have been reported from western part of country, namely Disphaerobius svenhedini (Verhoeff, 1934) Loksa, 1978, Hessebius styliferus (Loksa, 1978) and Schizotergitius altajicus Loksa, 1978(Loksa, 1965Farzalieva et al, 2017).…”
mentioning
confidence: 99%
“…The myriapod fauna of China is still poorly known and very little attention has been paid to the study of Lithobiomorpha, with only 74 species/subspecies hitherto known from the country (Ma et al 2014a, b, 2015; Minelli et al 2016; Pei et al 2014, 2015, 2016; Qin et al 2014). Xinjiang Autonomous Region is among the poorly studied regions of China with only eight species at present registered from its territory (Ma et al 2014b; Pei et al 2015, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, three species of Hessebius have been recorded (Ma et al 2014): H. jangtseanus (Verhoeff, 1942) distributed in Sanshenggou, Wolong Town, Wenchuan Country, Aba City, Sichuan Province; H. longispinipes Ma, Pei & Zhu, 2009 recorded in Xinjiang Uyghur Autonomous Region (Barkor country, Hami City) and H. multiforaminis Pei, Ma, Zapparoli & Zhu, 2010 recorded in Tibet Autonomous Region (Pulan country, Pulan Town, Ali City). Considering the geographic distribution of the species of Hessebius in China, their main habitat preference seems to be steppes, deserts or sub-deserts, and they are all seem to be native species.…”
Section: Introductionmentioning
confidence: 99%